A Community-Based Screening Tool for Childhood Epilepsy: Cross-Cultural Adaptation and Validation of the INDT-EPI Tool in Punjabi-Speaking Indian Population - Rajni Sharma; Sulena Sulena; Gagandeep Singh; Khushboo Bhagat; Tanvi Kiran; Abhay Partap Maurya; Sandeep Negi; Marami Das; Shikha Jain; Hobinder Arora; Sujiv Akkilagunta; Mehzabin Haider Hazarika; et al. (Annals of Indian Academy of Neurology)
Background and Objectives: Early diagnosis of epilepsy is crucial for improving outcomes. However, access to specialized healthcare remains a challenge in many regions. This study aimed to adapt and validate the International Clinical Epidemiology Network Diagnostic Tool for Epilepsy (INDT-EPI) for screening childhood epilepsy in the Punjabi-speaking Indian population. Methods: A cross-sectional study was conducted among parents of children aged 1–18 years. The INDT-EPI tool was translated into Punjabi, back-translated, and pilot-tested. Psychometric properties, including internal consistency, were assessed using Cronbach’s alpha. Test–retest reliability was assessed using the intraclass correlation coefficient (ICC) and Pearson correlation. Split-half reliability was evaluated using Spearman–Brown prophecy correlation coefficients. Sensitivity and specificity were calculated by comparing the findings of the INDT-EPI tool with clinical diagnoses. Results: The Punjabi version of the INDT-EPI tool demonstrated excellent cross-language concordance and robust psychometric properties. The tool’s internal consistency, as measured by Cronbach’s alpha, ranged from 0.904 to 1.000, indicating strong consistency across items. Test–retest reliability, assessed using ICC, ranged from 0.88 to 1.00, signifying excellent reliability. The Punjabi version of the INDT-EPI tool exhibited a high sensitivity of 86.6% (95% confidence interval [CI]: 79.2%–93.9%) and specificity of 87.1% (95% CI: 75.3%–98.9%). These findings suggest that the tool is a reliable and effective screening instrument for identifying children with epilepsy in Punjabi-speaking communities. Conclusions: The Punjabi version of the INDT-EPI tool is a reliable and consistent instrument for diagnosing epilepsy in children. Its excellent psychometric properties make it suitable for non-specialist healthcare providers. By enabling early diagnosis, it can improve patient outcomes and address the need for effective epilepsy diagnosis where specialized resources are scarce.